Rekonstruksi Filosofi Pendidikan Islam di Era Kecerdasan Artifisial: Analisis Pendekatan Sistem Maqāṣid Al-Sharī'ah Jasser Auda - Achsani Taqwim Zidni; Abdul Hafizh Syaichu; Adi Nurma Putranto (Jurnal Indonesia Kajian Pendidikan Islam, 2026)
Background: The disruption brought by Artificial Intelligence (AI), particularly Generative AI, poses an ontological challenge to Islamic education, as it risks reducing learning to mere data consumption while eroding teachers' spiritual authority. Objective: This study aims to reconstruct the philosophical foundations of Islamic education by synthesising the classical concept of adab with contemporary digital demands. Method: This research employs a qualitative library-based method using a philosophical hermeneutic approach, while adopting Jasser Auda’s Maqāṣid al Sharī‘ah systems framework as the analytical lens. The data were analysed from 41 reputable journal articles published between 2018 and 2025, along with classical turāṡ literature. Findings: The findings indicate that the automation of ta‘līm (knowledge transfer) by AI necessitates a paradigm shift toward ta’dīb (ethical internalisation) as the core function of education. By applying six features of Jasser Auda’s systems framework, particularly cognitiveness, openness, and purposefulness, this study formulates a “Digital Adab” framework to safeguard intellect (ḥifẓ al ‘aql) from algorithmic bias and AI hallucination phenomena. Conclusion: The study concludes that the teacher’s role must evolve from a mere instructor into a spiritual mentor (murabbī) who functions as a validator of truth. Contribution: This research contributes to the development of an “AI Maqāṣidī” educational model that positions technology not as an ultimate end, but as a wasīlah (means) governed by prophetic ethics to preserve human dignity in the post-human era.